Creating Social Enterprise for Ecological Art Exhibition - Jitpimolmard, Siriya; Tongkarnpanit, Panus; Chotipatthamanon, Sakonpat; Disatapundhu, Suppakorn (Journal of Humanities and Social Sciences, Rajapruk University, 2023)
This research objectives were to design and construction of a social enterprise for an ecological art exhibition and to design economic value added from Ecological Art Exhibition auction, bring income to develop the waste management system for riverside communities model and to develop pilot system expanded to other waterfront communities around the world. Where the main income would come from the auction of eco-art works exhibited such which were created by world-renowned artists and are in high demand. This was to create awareness among the general public. It is hoped that it can change the behavior of waste disposal and also solve the problem of waste that is contaminating the ecosystem today by using the proceeds from the auction of eco-art works that were displayed to develop a waste management system for a model riverside community to use extending to many waterfront communities around the world in the future. Data were analyzed using the Business Model Canvas and the Modern Marketing Model that combine traditional business knowledge with current technology to achieve research objectives. The results showed that 1) Thailand is well suited to be a leader for creating social enterprises. 2) Thailand is ready and has sufficient resources to be the center of the eco-exhibition economy. 3) This project can contribute to the reduction of water pollution problems in line with the concept of Sustainable Development Goals of the United Nations (2015) through the conservation of marine ecosystems, seas, oceans and sustainable reduction of the population of aquatic organisms. 4) Eco-art exhibitions can raise awareness and lead to change in people's behavior.